Negotiating hegemonic masculinity in Ian McEwan’s the cement garden - Li, Xueni; Awang, Mohammad Ewan; Ching, Florence Toh Haw (Universiti Putra Malaysia, 2025)
The late 20th century saw societal shifts and a reevaluation of gender identities, particularly in Western societies, which informed how writers rethought traditional notions of masculinity, heteronormative ideals, and family structure in their works. British writer Ian McEwan explores these issues through his novel, The Cement Garden (1978). While the novel’s portrayal of masculinity has received scholarly attention, this study posits that the reading of this theme could be further facilitated through the lens of hegemonic masculinity. Set against the socio-cultural and gender landscapes of 1970s Britain, the novel centers on Jack, a young male protagonist whose identity is shaped by the idealized yet troubled forms of masculinity. Drawing on Raewyn Connell’s concept of hegemonic masculinity as a configuration of gender practices, this study investigates the ways the novel depicts Jack’s relational struggle to achieve legitimacy and recognition within a fractured family environment. The analysis shows this process includes ambivalence towards and resistance to hegemonic masculinity, and exploration of alternative gender practices. Despite The Cement Garden’s provocative stance, this article argues that the novel is aware of both the potential and limitations of challenging hegemonic masculinity. Thus, it reflects on how, despite efforts, the specters of long held and entrenched Western ideals of masculinity remain ever-present and inevitable. This article contributes to the discussion on the representations of masculinity in fiction and how authors such as Ian McEwan engage with the contours of hegemonic masculinity and its repercussions on the construction of identity for young men.